Enhancing health and sports performance by design - Mohd Hasnun Arif, Hassan (Springer Nature, 2020)
This book gathers papers presented at the 2019 Movement, Health & Exercise (MoHE) Conference and International Sports Science Conference (ISSC). The theme of this year’s conference was "Enhancing Health and Sports Performance by Design". The content covers (but is not limited to) the following topics: exercise science; human performance; physical activity & health; sports medicine; sports nutrition; management & sports studies; and sports engineering & technology.